A The Dynamics of Motivation And Demotivation of Learning in Choosing The Study Interest of Islamic Religious Education Students - Anggraini, Fadhilla Nangroe; Shobahiya, Mahasri; Muhammad, Norshafiqah Binti (Universitas Muhammadiyah Surakarta, 2025)
Education Study Program (PAI) in higher education, with a focus on the University of Muhammadiyah Surakarta. Motivation is a crucial factor in academic decision-making, both intrinsic and extrinsic. Intrinsic motivation includes personal interest and a call from an early age to delve into religious knowledge and become an educator. Meanwhile, extrinsic motivation includes parental influence, social environment, and job prospects. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews with ten active students. The findings show that factors such as love for religious lessons, family support, aspirations to become teachers, and spiritual motivation such as the expectation of jariyah rewards are the main drivers. However, various demotivational factors also emerge, such as unclear study objectives, academic pressure, negative social influences, and mismatches between initial expectations and the reality of college. This condition contributes to a decrease in enthusiasm for learning and potential disruptions in the sustainability of studies. Nevertheless, the majority of respondents still view the profession of PAI teachers as a way of service that is full of spiritual values and not just seeking material gains. This research emphasizes the importance of a holistic understanding of student motivations and challenges to support academic coaching strategies and policies that are more humane, adaptive, and on target.